PENGAMBILAN KEPUTUSAN DALAM PENYEDIAAN HUNIAN LAYAK HUNI BAGI MASYARAKAT BERPENGHASILAN RENDAH DI JAKARTA SELATAN - Arya Wirawan Purnomo; Raflis Raflis; Ryan Faza Prasetyo (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2022)
Abstract The problem that comes from year to year in Jakarta is the high demand for housing, especially for Low-Income Communities. The DKI Jakarta Government has implemented a program that is expected to be able to answer these problems by carrying out a lot of simple flats for rent or simple flats for sale construction and providing subsidies to LowIncome Communities. There are 6 Criteria and 31 Sub-Criteria that underlie the selection of a residence. Analysis of the importance level of criteria segmented according to Low-Income Communities in South Jakarta, obtained by distributing questionnaires to 100 respondents, where the 3 criteria with the highest order are safe residence, flood-free living area, availability of clean water for daily needs. The data on the importance of criteria based on Low-Income Communities are then analyzed using the Analytical Hierarchy Process by asking 5 experts for the views of what is the best alternative for providing livable housing for Low-Income Communities in South Jakarta. The selection of the location for the construction is based on 5 experts, according to expert judgment Jl. Joe belongs to a relatively quiet area that meets the criteria for a safe place to live, in the Jl. Joe also has a water channel for flood prevention in accordance with the criteria for a flood-free area, while for the availability of clean water for daily needs, the three areas in the proposed alternative have relatively the same availability of clean water.